Stabilization of 960 nm laser using pound-drever-hall technique - Adhiwirawan, Made Surya (2012)
Frequency stabilization of 960 nm laser could not simply be done by using Doppler-free saturated absoption spectroscopy since there is no convenient atomic transition for locking a laser at that particular wavelength. We designed a system where a 780 nm laser that is locked at 5(2) S1/2 → 5(2) P3/2 trasition of Rubidium (Rb) atom can be used as primary reference to stabilize the length of a high ﬁnesse cavity. The stable cavity is then expected to be applied in a Pound-Drever-Hall technique for laser stabilization to lock the 960 nm laser.